Topic Development in the Freshman Engineering Paper: Finding a Focus. Issue 2 (3rd April 2019) - Eckel, Edward J.
ABSTRACT: Topic development and focus are relatively neglected areas of the student research process. This study examined how students in a freshman engineering writing class developed initial research paper topics into focused thesis statements. A mixed methods approach was used, incorporating online surveys, qualitative interviews, and a rubric to track topic development and assess thesis statement focus. The survey results and student comments indicated that participants were more competent at the mechanics of finding sources and writing than at developing appropriately scoped thesis statements. Closer collaboration between writing instructors and librarians is urged to more effectively support and scaffold topic development.